Intracameral recombinant tissue plasminogen activator (rtPA) as the primary treatment for secondary pupillary block - AR, Siti Noor Atikah; Mohd Khialdin, Safinaz; Mustapha, Mushawiahti; MS, Muhammad Syamil; MZ, Ayesha (Universiti Kebangsaan Malaysia. Faculty of Medicine, 2022)
Alteplase is a recombinant form of human tissue plasminogen activator (tPA) that converts plasminogen to plasmin essential for fibrinolysis. It is commonly used to treat embolic or thrombotic disorders such as ischemic stroke. Despite its rarity use in ophthalmology, we are reporting the effectiveness of recombinant tissue plasminogen activator (rtPA) in treating an eye with secondary pupillary block as a consequence of severe endophthalmitis. A patient presented with acute endophthalmitis after a complicated cataract extraction. Examination showed severe anterior chamber reaction leading to seclusion pupillae, iris bombe and presence of iridocorneal touch 360-degree. Following intracameral alteplase 2.5 microgram in 0.1 ml given, iris bombe was observed to resolve completely onehour later. Anterior chamber was also significantly deeper and slightly larger pupil compared to before rtPA injection. Due to clearer view of anterior segment, pars planar vitrectomy and extraction of intraocular lens could be performed with significant visual improvement after surgery. Our findings suggest that usage of rtPA, which is alteplase, was effective in treating secondary pupillary block due to intense anterior segment inflammation in endophthalmitis cases. Thus it is useful in replacing the conventional use of laser peripheral iridotomy in treating pupillary block, as the latter potentially aggravates the pre-existing inflammatory condition.